Student Perceptions of the Physical Education Study Program at Pattimura University on Online Learning During the Covid-19 Pandemic - Irfan Jaruddin; Emma Rumahlewang; Idris Moh Latar (International Journal of Education, Information Technology, and Others, 2021)
This study aims to find out how the perception of Unpatti Penjaskesrek study program students class 2018 and 2019 towards online learning during the Covid-19 Pandemic. The research method used is a survey. Survey research is used to collect information which is carried out by compiling a list of questions asked to respondents with a population of 2018 and 2019 Unpatti Penjaskesrek study program students. Sampling was carried out using probability sampling design. Then in the category of probability sampling technique the researcher used simple random technique. sampling. Collecting data using a questionnaire. Test the validity of the instrument using the product moment correlation and the reliability test using the Cronbach alpha formula. The results of the study regarding the perception of Unpatti's Penjaskesrek study program students towards online learning during the Covid-19 Pandemic were in the high category with a percentage of 74% or as many as 48 students. The number who entered the medium category was 26% or as many as 17 students and there was no response for the very high, low and very low categories. The data shows that students' perceptions are in the high category of online learning during the Covid-19 pandemic.